A multiple heat treatment method for TA15 titanium alloy formed by electron beam selective melting
Through multiple heat treatment, the martensite phase is decomposed and the non-equilibrium solidification structure is removed, which solves the problem of fluctuations in mechanical properties of TA15 titanium alloy with melt forming in the electron beam area, and improves the uniformity and strength of the alloy structure and performance.
Patent Information
- Application Number
- CN202311129788.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-09-04
AI Technical Summary
The electron beam selection melting forming TA15 titanium alloy has a problem of large fluctuation in the forming height direction, mainly due to the formation of unequal solidification structures, especially the existence of the martensite phase.
Multiple heat treatment methods are adopted, including phase transition heat treatment, supersaturated matrix formation heat treatment and secondary phase precipitation heat treatment, gradually decompose the martensite phase, remove the non-equilibrium solidified structure, and form a uniform equiaxed α phase and supersaturated β matrix.
Through multiple heat treatment, the mechanical properties uniformity of TA15 titanium alloy is significantly improved, the overall strength is enhanced, and the performance fluctuations in the forming height direction are avoided.
Smart Images

Figure CN117001013B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal additive manufacturing and relates to a multiple heat treatment method for electron beam selective melting forming TA15 titanium alloy. Background Art
[0002] TA15 titanium alloy is a typical near-α titanium alloy with a composition of Ti-6Al-2Zr-1Mo-1V. It has moderate room temperature strength, excellent high temperature strength and good thermal stability. It can maintain good mechanical properties at 500°C and has broad application prospects in important fields such as aerospace.
[0003] TA15 titanium alloy is difficult to process. Aerospace structural parts are complex and require high precision. For example, parts such as rudder wings, compressor discs, and blades have a long preparation cycle and high cost using traditional methods. How to quickly develop qualified TA15 titanium alloy components has important research value in the aerospace field. Compared with traditional methods such as integral forging, electron beam selective melting to form large and complex titanium alloy components has obvious technical and economic advantages such as digitization, precision, and design-material-manufacturing integration. The use of electron beam selective melting technology to realize the manufacture of complex structural parts of difficult-to-process materials such as TA15 titanium alloy has broad application prospects in the aerospace field.
[0004] However, electron beam selective melting technology is a process method of point-by-point forming, line-by-line overlapping, and layer-by-layer accumulation. After the molten pool is formed in a short time, it quickly spreads and solidifies on the substrate, showing the characteristics of rapid solidification organization. Under certain process conditions, it is inevitable to form a non-equilibrium solidification organization such as martensite. This non-equilibrium solidification organization is unstable, so the parts formed by it often have a series of problems, such as uneven alloy organization, large fluctuations in mechanical properties at different positions along the forming height direction, etc. These problems are difficult to completely eliminate only by optimizing the processing technology, and the organizational properties of the formed parts need to be further improved through subsequent treatment. Summary of the invention
[0005] In order to solve the problem that the mechanical properties of TA15 titanium alloy formed by the existing electron beam selective melting process fluctuate greatly at different positions along the forming height direction, the present invention proposes a processing method, which can promote the complete decomposition of the martensite phase through multiple heat treatments without taking special process means such as metamorphic treatment, remove the non-equilibrium solidification structure and obtain an alloy with uniform performance.
[0006] The multiple heat treatment method of the electron beam selective melting forming TA15 titanium alloy of the present invention is carried out according to the following steps:
[0007] Step 1: Prepare a TA15 titanium alloy specimen by electron beam selective melting additive manufacturing process and cool it to room temperature, with an electron beam current of 4-9 mA, a scanning speed of 0.8-1.4 m / s, and a ratio of electron beam current to scanning speed of <5.8; obtain an electron beam selective melting-formed TA15 titanium alloy containing a martensite phase;
[0008] Step 2: Use an air furnace or a vacuum furnace to perform phase transformation heat treatment on the TA15 titanium alloy formed by electron beam selective melting, keep it warm for a period of time and then cool it to room temperature;
[0009] The phase transformation heat treatment temperature is 1250-1260K;
[0010] The phase transformation heat treatment holding time is 1 to 1.5 hours;
[0011] The phase transformation heat treatment cooling method is furnace cooling; the cooling rate is 0.05K / s to 1K / s; because the cooling rate in the furnace cooling process is the slowest, the α phase in the organization has sufficient time and energy to grow. And in the process of slow cooling rate, β→α transformation occurs to obtain a large amount of equiaxed α phase.
[0012] Step 3: performing a supersaturated matrix forming heat treatment on the TA15 titanium alloy formed by electron beam selective melting obtained in step 2, and cooling to room temperature after keeping the temperature for a period of time; the temperature of the supersaturated matrix forming heat treatment is lower than the temperature of the phase transformation heat treatment;
[0013] The supersaturated matrix forming heat treatment temperature is 1190-1200K;
[0014] The supersaturated matrix forming heat treatment holding time is 1 to 1.5 hours;
[0015] The supersaturated matrix formation heat treatment cooling method is air cooling; the cooling rate is 1 to 3 K / s; after keeping at 1190 to 1200 K, part of the α phase is transformed into the β phase again. Since the air cooling process has a fast cooling rate, as the cooling rate increases, the thickness of the lamellae in the mixed structure decreases, the blocky α phase gradually decreases and disappears, and a supersaturated β matrix is formed.
[0016] Step 4: Perform secondary phase precipitation heat treatment on the electron beam selective melting formed TA15 titanium alloy obtained in step 3, keep it warm for a period of time and then cool it to room temperature; the temperature of the secondary phase precipitation heat treatment is lower than the temperature of the supersaturated matrix formation heat treatment.
[0017] The secondary phase precipitation heat treatment temperature is 870-880K;
[0018] The secondary phase precipitation heat treatment holding time is 3.5 to 4 hours;
[0019] The secondary phase precipitation heat treatment cooling method is air cooling, and the cooling rate is 1-3K / s. Because the cooling rate is faster during air cooling, a larger degree of supercooling is formed in the structure, and the secondary α phase is precipitated at a faster cooling rate.
[0020] The principle of the present invention is:
[0021] In the existing electron beam selective melting process for forming titanium alloys, the extremely high temperature gradient and cooling rate in the molten pool are prone to form non-steady-state structures. Under certain process parameters, a martensite phase will be formed on the sample surface. Due to the existence of substructures such as dislocations and twins in the martensite phase, the mechanical properties are greatly different from those at the position without the martensite phase, which will eventually cause the inhomogeneity of the alloy structure and properties. In view of the above problems, in the multiple heat treatment process of the present invention, the electron beam selective melting forming TA15 titanium alloy is kept at 1250-1260 near the β phase transformation point for 1-1.5 and then furnace cooled. The martensite phase in the alloy is completely decomposed and a large amount of equiaxed α phase is obtained. Subsequently, after keeping at 1190-1200K, part of the α phase is transformed back into the β phase, and a supersaturated β matrix is formed during the cooling process. Finally, after aging at 870-880K for 3.5-4h, secondary α is precipitated from the matrix. s phase; the holding time and cooling method of each multiple heat treatment have an important influence on the morphology and size of the α phase, and long-term heat preservation leads to the complete decomposition of the martensite phase, which improves the overall strength while ensuring the uniformity of the overall structure and performance of the sample. Therefore, the present invention performs multiple heat treatments on the TA15 titanium alloy formed by electron beam selective melting in the printing process in which a martensite phase is generated, so as to promote the decomposition of the martensite phase and make the alloy structure and performance more uniform, thereby avoiding the problem of large performance fluctuations at different positions of the printed alloy. After multiple heat treatments, the overall strength of the sample in which the martensite phase has been decomposed is still better than that of the sample in which no martensite phase is generated in the printing process and which has not been heat treated. The method of the present invention provides the possibility for rapid, low-cost, and high-quality additive manufacturing of TA15 titanium alloy parts, and has broad application prospects and economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a microstructure photo of the additively manufactured TA15 titanium alloy before heat treatment (Example 1, containing martensite phase);
[0023] Figure 2 This is a microstructure photo of the additively manufactured TA15 titanium alloy before heat treatment (comparative example, does not contain martensite phase);
[0024] Figure 3 This is a microstructure photo of the additively manufactured TA15 titanium alloy in the height direction before heat treatment;
[0025] Figure 4The engineering stress-strain curves of additively manufactured TA15 titanium alloy at different positions in the height direction before heat treatment;
[0026] Figure 5 This is a microstructure photo of the free surface of the additively manufactured TA15 titanium alloy after 1253K / 1h / furnace hot and cold treatment;
[0027] Figure 6 This is a microstructure photograph of the free surface of the additively manufactured TA15 titanium alloy after heat treatment at 1253K / 1h / furnace cooling + 1193K / 1h / air cooling + 873K / air cooling. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0029] Specific implementation method 1: The multiple heat treatment method of TA15 titanium alloy formed by electron beam selective melting in this implementation method is carried out according to the following steps:
[0030] Step 1: Prepare a TA15 titanium alloy specimen by electron beam selective melting additive manufacturing process and cool it to room temperature, with an electron beam current of 4-9 mA, a scanning speed of 0.8-1.4 m / s, and a ratio of electron beam current to scanning speed of <5.8; obtain an electron beam selective melting-formed TA15 titanium alloy containing a martensite phase;
[0031] Step 2: Use an air furnace or a vacuum furnace to perform phase transformation heat treatment on the TA15 titanium alloy formed by electron beam selective melting, keep it warm for a period of time and then cool it to room temperature;
[0032] The phase transformation heat treatment temperature is 1250-1260K;
[0033] The phase transformation heat treatment holding time is 1 to 1.5 hours;
[0034] The phase transformation heat treatment cooling method is furnace cooling; the cooling rate is 0.05K / s to 1K / s;
[0035] Step 3: performing a supersaturated matrix forming heat treatment on the TA15 titanium alloy formed by electron beam selective melting obtained in step 2, and cooling to room temperature after keeping the temperature for a period of time; the temperature of the supersaturated matrix forming heat treatment is lower than the temperature of the phase transformation heat treatment;
[0036] The supersaturated matrix forming heat treatment temperature is 1190-1200K;
[0037] The supersaturated matrix forming heat treatment holding time is 1 to 1.5 hours;
[0038] The supersaturated matrix forming heat treatment cooling method is air cooling; the cooling rate is 1 to 3K / s;
[0039] Step 4: performing secondary phase precipitation heat treatment on the TA15 titanium alloy formed by electron beam selective melting obtained in step 3, and cooling to room temperature after keeping the temperature for a period of time;
[0040] The secondary phase precipitation heat treatment temperature is 870-880K;
[0041] The secondary phase precipitation heat treatment holding time is 3.5 to 4 hours;
[0042] The secondary phase precipitation heat treatment cooling method is air cooling; the cooling rate is 1 to 3 K / s.
[0043] In the existing electron beam selective melting process of titanium alloy, the extremely high temperature gradient and cooling rate in the molten pool are prone to form non-steady-state structures. Under certain process parameters, a martensite phase will be formed on the surface of the sample. Due to the existence of substructures such as dislocations and twins in the martensite phase, the mechanical properties are quite different from those at the position without the martensite phase, which will eventually cause the inhomogeneity of the alloy structure and properties. In view of the above problems, in the multiple heat treatment process of this embodiment, the electron beam selective melting forming TA15 titanium alloy is kept at 1250-1260 near the β phase transformation point for 1-1.5 and then furnace cooled. The martensite phase in the alloy is completely decomposed and a large amount of equiaxed α phase is obtained. Subsequently, after keeping at 1190-1200K, part of the α phase is transformed into the β phase again, and a supersaturated β matrix is formed during the cooling process. Finally, after aging at 870-880K for 3.5-4h, secondary α is precipitated from the matrix. s phase; the holding time and cooling method of each multiple heat treatment have an important influence on the morphology and size of the α phase, and the long-term holding time leads to the complete decomposition of the martensite phase, which improves the overall strength and removes the non-equilibrium solidification structure. Therefore, this embodiment performs multiple heat treatments on the TA15 titanium alloy formed by electron beam selective melting in which a martensite phase is generated during the printing process, so as to promote the decomposition of the martensite phase and make the alloy structure and properties more uniform, thereby avoiding the problem of large performance fluctuations at different positions of the printed alloy. After multiple heat treatments, the overall strength of the sample in which the martensite phase has been decomposed is still better than that of the sample in which no martensite phase is generated during the printing process and which has not been heat treated. The method of this embodiment provides the possibility for rapid, low-cost, and high-quality additive manufacturing of TA15 titanium alloy parts, and has broad application prospects and economic value.
[0044] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the phase transformation heat treatment temperature in step 2 is 1253K.
[0045] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the holding time of the phase transformation heat treatment in step two is 1 hour.
[0046] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: the cooling method of the phase transformation heat treatment in step 2 is furnace cooling; the cooling rate is 0.05K / s.
[0047] Specific implementation method five: This implementation method is different from any one of specific implementation methods one to four in that: the heat treatment temperature for forming the supersaturated matrix in step three is 1193K.
[0048] Specific implementation method six: This implementation method is different from any one of specific implementation methods one to five in that: the heat treatment holding time for forming the supersaturated matrix in step three is 1 hour.
[0049] Specific implementation method seven: This implementation method is different from any one of specific implementation methods one to six in that: the cooling method of the supersaturated matrix formation heat treatment in step three is air cooling; the cooling rate is 2K / s.
[0050] Specific embodiment eight: This embodiment differs from any one of specific embodiments one to seven in that: the secondary phase precipitation heat treatment temperature in step four is 873K.
[0051] Specific implementation method 9: The difference between this implementation method and any one of specific implementation methods 1 to 8 is that the holding time of the secondary phase precipitation heat treatment in step 4 is 3.5 hours.
[0052] Specific implementation method ten: This implementation method is different from any one of specific implementation methods one to nine in that: the cooling method of the secondary phase precipitation heat treatment in step four is air cooling; the cooling rate is 2K / s.
[0053] Embodiment 1:
[0054] The TA15 titanium alloy sample with a rectangular structure was formed by electron beam selective melting, with a length of 20 mm, a width of 20 mm, and a height of 5 mm. The implementation steps are as follows:
[0055] Step 1: Ti-6.5Al-2Zr-1Mo-1V (TA15) alloy powder was prepared by electrode induction melting gas atomization method and then heated to 2×10 -3 Electron beam selective melting is performed in a mBar high vacuum environment, with a beam current of 8mA and a scanning speed of 1.4m / s;
[0056] Step 2: The substrate is austenitic stainless steel, and TA15 powder is filled around the substrate to ensure that the substrate will not be scraped by the powder brush during the forming process. At the same time, the lower thermal conductivity of the powder provides a certain insulation effect for the substrate during the printing process. Before printing begins, a defocused current is used to preheat the substrate in a checkerboard cycle. The substrate temperature is monitored in real time by a thermocouple attached to the center of the bottom of the substrate. When the temperature reaches about 750°C, preheating is stopped and the first layer of powder is started. The powder thickness is 75μm, and the powder bed is preheated using a high-speed defocused electron beam for rapid heating, which causes the powder to be slightly sintered to increase the conductivity of the powder and avoid the mutual repulsion of the powder ("powder blowing") caused by charge accumulation. During the sample forming process, the scanning strategy is to rotate the scanning direction of two adjacent passes by 180° and the scanning direction of two adjacent layers by 90° to form a TA15 component;
[0057] Step 3: Clean the surface of the specimen with anhydrous ethanol, remove the metal powder on the surface and then dry it;
[0058] Step 4: Study the microstructure of the formed part at different positions along the deposition height direction, such as Figures 1 to 3 As shown, the phase morphology near the top area changes significantly, and the lamellar phase transforms into the needle-like martensite phase;
[0059] Step 5: The microstructure of the formed part at different positions along the deposition height direction is studied, and its tensile properties are shown in Table 1, where the S5 sample represents the free surface area in contact with the vacuum environment. From the data in the table, it can be seen that the formation of the martensite phase has an impact on the mechanical properties of the component, and the strength of the sample where the martensite phase is formed is higher;
[0060] Step 6: Heat treatment of the additively manufactured TA15 alloy component: 1253K / 1h / furnace cooling + 1193K / 1h / air cooling + 873K / air cooling;
[0061] ①, using air furnace or vacuum furnace to perform phase transformation heat treatment on TA15 titanium alloy formed by electron beam selective melting, and cooling to room temperature after keeping warm for a period of time; the phase transformation heat treatment temperature is 1253K; the holding time is 1h; the cooling method is furnace cooling; the cooling rate is 0.05K / s;
[0062] ②, subjecting the TA15 titanium alloy formed by electron beam selective melting obtained in step ① to supersaturated matrix formation heat treatment, and cooling to room temperature after keeping the temperature for a period of time; the temperature of the supersaturated matrix formation heat treatment is lower than the temperature of the phase transformation heat treatment; the supersaturated matrix formation heat treatment temperature is 1193K; the holding time is 1h; the cooling method is air cooling; the cooling rate is 2K / s;
[0063] ③. Perform secondary phase precipitation heat treatment on the TA15 titanium alloy formed by electron beam selective melting obtained in step ②, and cool to room temperature after keeping warm for a period of time; the temperature of secondary phase precipitation heat treatment is lower than the temperature of supersaturated matrix formation heat treatment. The secondary phase precipitation heat treatment temperature is 873K; the holding time is 3.5h; the cooling method is air cooling; the cooling rate is 2K / s;
[0064] Step 7: Observe the microstructure of the alloy sample after multiple heat treatments, such as Figure 5 and Figure 6 As shown, it can be seen that the martensite phase is completely decomposed after multiple heat treatments and long-term heat preservation.
[0065] Due to the formation of the martensite phase near the free surface, the alloy components are prone to uneven mechanical properties in the height direction. The formation of the martensite phase α′ can significantly improve the tensile strength of the sample. The uneven distribution of the martensite phase in the sample and the stress concentration at the α′ / α and α′ / β interfaces during deformation lead to reduced plasticity of the sample. Multiple heat treatment processes can promote the decomposition of the martensite phase at the free surface of the additively manufactured TA15 titanium alloy, thereby making the mechanical properties of the alloy components more uniform. And according to the tensile strength values of the three layers S2, S3, and S4, it can be obtained that the average tensile strength of the sample after the martensite phase decomposition can reach 1047MPa;
[0066] Compared with the TA15 alloy (comparative example) prepared by electron beam selective melting without multiple heat treatment and without martensite phase (beam current 7mA, scanning speed 1.2m / s), the tensile strength of the alloy treated in this embodiment is increased by 8.8% at the same height, indicating that the present invention is suitable for processing samples containing martensite phase and can obtain higher strength.
[0067] Figure 1 This is a microstructure photo of the additively manufactured TA15 titanium alloy before heat treatment (containing martensite phase); Figure 2 This is a microstructure photo of the additively manufactured TA15 titanium alloy before heat treatment (without martensite phase); Figure 3 The microstructure photos of the additively manufactured TA15 titanium alloy in the height direction before heat treatment; Figure a shows different sampling positions in the height direction; Figures b to f correspond to the microstructure photos of the additively manufactured TA15 titanium alloy at positions S1 to S5; Figures 1 to 3 It can be shown that before multiple heat treatments, martensite phase appeared near the free surface of the additively manufactured TA15 titanium alloy. Figure 4 The engineering stress-strain curves of additively manufactured TA15 titanium alloy at different positions in the height direction before heat treatment; Figure 4 This indicates that the formation of the martensite phase has an impact on the mechanical properties of the alloy, resulting in significant differences in the mechanical properties of the alloy at different heights. Figure 5This is a microstructure photo of the free surface of the additively manufactured TA15 titanium alloy after 1253K / 1h / furnace hot and cold treatment; Figure 6 This is a microstructure photograph of the free surface of the additively manufactured TA15 titanium alloy after heat treatment at 1253K / 1h / furnace cooling + 1193K / 1h / air cooling + 873K / air cooling. Figure 5 and Figure 6 This can explain that the martensite phase is completely decomposed after multiple heat treatments and long-term heat preservation.
[0068] Table 1
[0069]
[0070] Embodiment 2:
[0071] The difference between this embodiment and the embodiment is that the process of heat treatment of the additively manufactured TA15 alloy component in step 6 is:
[0072] ①, using air furnace or vacuum furnace to perform phase transformation heat treatment on TA15 titanium alloy formed by electron beam selective melting, and cooling to room temperature after keeping warm for a period of time; the phase transformation heat treatment temperature is 1255K; the holding time is 1h; the cooling method is furnace cooling; the cooling rate is 0.06K / s;
[0073] ②, subjecting the TA15 titanium alloy formed by electron beam selective melting obtained in step ① to supersaturated matrix formation heat treatment, and cooling to room temperature after keeping the temperature for a period of time; the temperature of the supersaturated matrix formation heat treatment is lower than the temperature of the phase transformation heat treatment; the supersaturated matrix formation heat treatment temperature is 1195K; the holding time is 1h; the cooling method is air cooling; the cooling rate is 2K / s;
[0074] ③. Perform secondary phase precipitation heat treatment on the TA15 titanium alloy formed by electron beam selective melting obtained in step ②, and cool to room temperature after keeping warm for a period of time; the temperature of secondary phase precipitation heat treatment is lower than the temperature of supersaturated matrix formation heat treatment. The secondary phase precipitation heat treatment temperature is 880K; the holding time is 3.5h; the cooling method is air cooling; the cooling rate is 2K / s;
[0075] The other processes and parameters are the same as those in Example 1.
[0076] The average tensile strength of the TA15 titanium alloy formed by electron beam selective melting after treatment in Example 2 can reach 1050 MPa.
[0077] Embodiment 3:
[0078] The difference between this embodiment and the embodiment is that the process of heat treatment of the additively manufactured TA15 alloy component in step 6 is:
[0079] ①, using air furnace or vacuum furnace to perform phase transformation heat treatment on TA15 titanium alloy formed by electron beam selective melting, and cooling to room temperature after keeping warm for a period of time; the phase transformation heat treatment temperature is 1260K; the holding time is 1h; the cooling method is furnace cooling; the cooling rate is 0.05K / s;
[0080] ②, subjecting the TA15 titanium alloy formed by electron beam selective melting obtained in step ① to supersaturated matrix formation heat treatment, keeping the heat for a period of time and then cooling to room temperature; the temperature of the supersaturated matrix formation heat treatment is lower than the temperature of the phase transformation heat treatment; the supersaturated matrix formation heat treatment temperature is 1198K; the holding time is 1h; the cooling method is air cooling; the cooling rate is 2K / s;
[0081] ③. Perform secondary phase precipitation heat treatment on the TA15 titanium alloy formed by electron beam selective melting obtained in step ②, and cool to room temperature after keeping warm for a period of time; the temperature of secondary phase precipitation heat treatment is lower than the temperature of supersaturated matrix formation heat treatment. The secondary phase precipitation heat treatment temperature is 875K; the holding time is 3.5h; the cooling method is air cooling; the cooling rate is 2K / s;
[0082] The other processes and parameters are the same as those in Example 1.
[0083] The average tensile strength of the TA15 titanium alloy formed by electron beam selective melting after treatment in Example 3 can reach 1044 MPa.
Claims
1. A multiple heat treatment method for TA15 titanium alloy formed by electron beam selective melting, characterized in that: The multiple heat treatment method of TA15 titanium alloy formed by electron beam selective melting is carried out in the following steps: Step 1: Prepare a TA15 titanium alloy specimen by electron beam selective melting additive manufacturing process and cool it to room temperature, with an electron beam current of 4-9 mA, a scanning speed of 0.8-1.4 m / s, and a ratio of electron beam current to scanning speed of <5.8; obtain an electron beam selective melting-formed TA15 titanium alloy containing a martensite phase; Step 2: Use an air furnace or a vacuum furnace to perform phase transformation heat treatment on the electron beam selectively melted TA15 titanium alloy, keep it warm for a period of time and then cool it to room temperature; the martensite phase in the alloy is completely decomposed and an equiaxed α phase is obtained; The phase transformation heat treatment temperature is 1250-1260K; The phase transformation heat treatment holding time is 1 to 1.5 hours; The phase transformation heat treatment cooling method is furnace cooling; the cooling rate is 0.05K / s to 1K / s; Step 3: performing a supersaturated matrix forming heat treatment on the electron beam selective melting formed TA15 titanium alloy obtained in step 2, and cooling to room temperature after keeping the temperature for a period of time; the temperature of the supersaturated matrix forming heat treatment is lower than the temperature of the phase transformation heat treatment; part of the α phase is transformed into the β phase again, and a supersaturated β matrix is formed during the cooling process; The supersaturated matrix forming heat treatment temperature is 1190-1200K; The supersaturated matrix forming heat treatment holding time is 1 to 1.5 hours; The supersaturated matrix forming heat treatment cooling method is air cooling; the cooling rate is 1 to 3K / s; Step 4: The TA15 titanium alloy obtained by electron beam selective melting in step 3 is subjected to secondary phase precipitation heat treatment, and then cooled to room temperature after being kept warm for a period of time; secondary α s Mutually; The secondary phase precipitation heat treatment temperature is 870-880K; The secondary phase precipitation heat treatment holding time is 3.5 to 4 hours; The secondary phase precipitation heat treatment cooling method is air cooling; the cooling rate is 1 to 3 K / s.
2. The multiple heat treatment method for electron beam selective melting forming TA15 titanium alloy according to claim 1, characterized in that: The phase transformation heat treatment temperature in step 2 is 1253K.
3. The multiple heat treatment method for forming TA15 titanium alloy by electron beam selective melting according to claim 1, characterized in that: The phase transformation heat treatment holding time in step 2 is 1 hour.
4. The multiple heat treatment method for forming TA15 titanium alloy by electron beam selective melting according to claim 1, characterized in that: The cooling method of the phase transformation heat treatment in step 2 is furnace cooling; the cooling rate is 0.05K / s.
5. The multiple heat treatment method for TA15 titanium alloy formed by electron beam selective melting according to claim 1, characterized in that: The heat treatment temperature for forming the supersaturated matrix in step 3 is 1193K.
6. The multiple heat treatment method for TA15 titanium alloy formed by electron beam selective melting according to claim 1, characterized in that: The heat treatment holding time for forming the supersaturated matrix in step 3 is 1 hour.
7. The multiple heat treatment method for TA15 titanium alloy formed by electron beam selective melting according to claim 1, characterized in that: The cooling method for the supersaturated matrix formation heat treatment in step 3 is air cooling; the cooling rate is 2K / s.
8. The multiple heat treatment method for TA15 titanium alloy formed by electron beam selective melting according to claim 1, characterized in that: The secondary phase precipitation heat treatment temperature in step 4 is 873K.
9. The multiple heat treatment method for TA15 titanium alloy formed by electron beam selective melting according to claim 1, characterized in that: The holding time of the secondary phase precipitation heat treatment in step 4 is 3.5 hours.
10. The multiple heat treatment method for TA15 titanium alloy formed by electron beam selective melting according to claim 1, characterized in that: The cooling method of the secondary phase precipitation heat treatment in step 4 is air cooling; the cooling rate is 2K / s.
Citation Information
Patent Citations
Heat treatment method for obtaining tri-state structure in SLM forming titanium alloy
CN113275600A